The relationship between plasma amyloid-β peptides and the medial temporal lobe in the homebound elderly - Sun, Xiaoyan (Int J Geriatr Psychiatry, 2010)
BACKGROUND: The ratio of high amyloid-β peptide40 (Aβ40) and low Aβ42 in plasma predicts the risk of Alzheimer’s disease (AD) and is associated with episodic recall in depression. We thus examined the relationship between plasma Aβ levels and brain volumes. METHODS: Homebound elders (N = 352) who had undergone brain MRI were used. Plasma Aβ1-40 and Aβ1-42 were measured by ELISA. Volumes of medial temporal regions, including the amygdala and hippocampus, were manually measured. RESULTS: Amygdala volume was associated with log(10) of plasma Aβ1-42 (β = + 0.19, SE = 0.07, p = 0.005) after adjusting for AD, infarcts, white matter hyperintensities and demographics. In the absence of dementia, decreasing quartiles of plasma Aβ1-42 (Mean + SD ml: Q4 = 4.1±0.8; Q3 = 3.9±0.7; Q2 = 3.6 ± 0.8 and Q1 = 3.7 ± 0.8, p = 0.01) and increasing quartiles of plasma Aβ1-40/l-42 ratio were associated with smaller amygdala volume. Those depressed subjects with a high plasma Aβ1-40/1–42 ratio had smaller amygdala (Mean + SD ml: 3.3 ±0.8 vs. 3.6 ±0.8, p = 0.04) and total brain volume (Mean + SD liter: 0.95 ±0.07 vs. 1.04 ± 0.12, p = 0.005), and had a higher rate of MCI (67 vs. 36%, p = 0.02) than those with a low plasma Aβ1-40/l-42 ratio. CONCLUSIONS: The combination of low plasma Aβ1-42 concentration and atrophy of the medial temporal lobe structures, which regulates mood and cognition, may represent a biomarker for a prodromal stage of AD.